2008
DOI: 10.1016/j.jvs.2007.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Target lesion ulceration and arch calcification are associated with increased incidence of carotid stenting-associated ischemic lesions in octogenarians

Abstract: Increased prevalences of severe aortic arch calcifications and target lesion ulceration are associated with an increased risk for magnetic resonance DWI-detected embolic events during CAS. Because in our study arch calcification and target lesion ulceration were more prevalent in octogenarians, this association may explain the increased risk of CAS in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 35 publications
2
44
2
Order By: Relevance
“…Our study has confirmed that patients with a symptomatic carotid lesion constitute a riskier population subgroup, as previously reported elsewhere. 22,25 The highly significant correlation between outcome and age seen in other studies, 9,15,16,18,22 with a particularly high complication rate in patients aged 80 years or older, was not confirmed by our data. CAS is still indicated for patients older than 80 years in our center.…”
Section: Discussioncontrasting
confidence: 71%
“…Our study has confirmed that patients with a symptomatic carotid lesion constitute a riskier population subgroup, as previously reported elsewhere. 22,25 The highly significant correlation between outcome and age seen in other studies, 9,15,16,18,22 with a particularly high complication rate in patients aged 80 years or older, was not confirmed by our data. CAS is still indicated for patients older than 80 years in our center.…”
Section: Discussioncontrasting
confidence: 71%
“…This finding is consistent with that of a recent meta-analysis of outcomes after stenting and endarterectomy in elderly patients 34 and may be explained by the increased calcification and tortuosity of the supra-aortic branches in older patients. [35][36][37] Although the results of CREST suggest a possible benefit with stenting in patients aged <70 years old, 10 no difference in stroke rate was observed in younger patients when data were pooled across trials. 3 Some trials have also suggested that treatment effects may differ in men and women, 11,38,39 and there is currently no consensus for management of carotid stenosis in women.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the aging population has presented new treatment challenges. [18][19][20][21][22][23][24] In particular, recent data suggest that octogenarians are at particularly high risk for CAS, 20,23,24 though various single-center experiences have reported the safety of CAS in this subgroup. 19,21,21,25,26 In this report of the 4-year outcomes of the CaRESS trial, we examine the CMS coverage guidelines for CAS in a series of subgroup analyses that stratify this large, broad-risk patient cohort by risk status, symptomatology, stenosis grade, and age .80 years.…”
Section: ¤ ¤mentioning
confidence: 99%